Individual and combined associations of alanine aminotransferase and hemoglobin with metabolic syndrome in the elderly in Qingdao, China - Liu, Li; Shao, Yuhan; Feng, Enqiang; Shao, Zhugang; Xing, Dongming (Frontiers in Medicine, 2023)
Background and aims: Combined associations of alanine aminotransferase (ALT) and hemoglobin (Hb) with metabolic syndrome (MetS) have not been assessed yet.The current study investigated the independent and combined relationships between ALT, Hb and MetS in the elderly.The 37,966 elderly participants aged 65 years and older were recruited from community centers in Qingdao, China. The sampled elderly population visited the health centers once a year where they were offered a free health checkup. Based on a combination of ALT and Hb levels categorized by tertile, participants were grouped into nine groups (Group 1-9). Logistic regression models were used to analyze the individual and combined associations of ALT and Hb with MetS.Results: ALT and Hb were both independently related to MetS in both genders. With the elevation of ALT or Hb levels, risks for MetS and its components increased.Compared to the reference group (the 1st tertiles of both ALT and Hb levels), respective odds ratio of combined ALT and Hb for MetS in Group 2-9 ranged from 1.32-3.38 and 1.14-2.31 in men and women after adjusting for age, sex, education, married status, current smoking, current drinking, physical activity and diet habit.Conclusions: ALT and Hb were both independently related to MetS and its components. Combined ALT and Hb levels could increase risks of MetS and its components than an elevation in ALT or Hb alone.